SM Vooruit nr. 1 is nu 90 jaar ! - Roels, Germain; Temmerman, Gilbert; Lambert, Paul; Bracke, Albert (Brussel: Febecoop, 1971)
"Speciaal nummer van Coöperatie, (1971) april. ; Archief SM Vooruit Archief Febecoop"